Extracytoplasmic Function Sigma Factors Governing Production of the Primary Siderophores in Pathogenic Burkholderia Species - Grove, Anne (Frontiers in Microbiology, 2022)
Bacteria respond to changing environments by modulating their gene expression programs. One of the mechanisms by which this may be accomplished is by substituting the primary  factor with an alternative  factor belonging to the family of extracytoplasmic function (ECF)  factors. ECF  factors are activated only in presence of specific signals, and they direct the RNA polymerase to transcribe a defined subset of genes. One condition, which may trigger the activation of an ECF  factor is iron limitation. To overcome iron starvation, bacteria produce and secrete siderophores, which chelate iron and facilitate its cellular uptake. In the genus Burkholderia, which includes several serious human pathogens, uptake of iron is critical for virulence, and expression of biosynthetic gene clusters encoding proteins involved in synthesis and transport of the primary siderophores are under control of an ECF  factor. This review summarizes mechanisms involved in regulation of these gene clusters, including the role of global transcriptional regulators. Since siderophore-mediated iron acquisition is important for virulence, interference with this process constitutes a viable approach to the treatment of bacterial infections.